Clinical performance of one shade universal composite resin and nanohybrid composite resin as full coronal esthetic restorations in primary maxillary incisors: A randomized controlled trial - Zulekha; C Vinay; K S Uloopi; Kakarla Sri RojaRamya; Chaitanya Penmatsa; M V Ramesh (Wolters Kluwer Medknow Publications, 2022)
Background: Strip crowns are the first treatment of choice for restoring anterior teeth affected with early childhood caries. However, shade matching of resin composites is still an issue. The broad color matching ability of a recently introduced single shade composite, Omnichroma eliminates the need for shade-matching procedure, reduces composite inventory, and minimizes chair-side time. Aim: The aim is to evaluate the color match, color stability, and retention of one shade universal composite resin, Omnichroma and nanohybrid resin composite, Tetric-N-Ceram. Settings and Design: The study design involves split-mouth randomized controlled trial. Materials and Methods: The study was conducted on 25 children aged 3-5 years with multi-surface caries lesions in primary maxillary anterior teeth. Teeth were allocated to two groups randomly: Group 1 - One shade universal composite, Omnichroma (n = 25), Group 2 - Nanohybrid composite, Tetric-N-Ceram (n = 25). After caries excavation and tooth preparation, teeth were restored with corresponding materials using strip crowns. Color match at baseline, color stability, and retention after 6- and 12-month follow-up were evaluated using the Modified United States Public Health Services criteria. Statistical Analysis: The Mann-Whitney U test and Wilcoxon signed-rank test were used to analyze the data. Results: On comparison of Omnichroma and Tetric-N-Ceram groups, no statistically significant difference was observed in the color match at baseline (P = 0.716) as well as color stability (P = 0.575 at 6 months and 0.990 at 12 months) and retention (P = 0.153 at 6 months and 0.226 at 12 months) at both 6- and 12-month intervals. On intragroup comparison, the difference in the color stability at 6 and 12-month interval was statistically significant (P = 0.001) for both the groups, indicating that the color stability of restorations was better at 6-month interval compared to 12-month interval. In both Omnichroma and Tetric-N-Ceram groups, retention of restorations was better at 6-month interval compared to 12-month interval and this difference was statistically significant (P = 0.025 and 0.014, respectively). Conclusion: The clinical performance of Omnichroma in terms of color match, color stability, and retention was comparable to nanohybrid composite, Tetric-N-Ceram.